2014
DOI: 10.1155/2014/560802
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Neuromodulation at Posterior Tibial Nerve and ST36 for Chronic Constipation

Abstract: The aims of this study were to investigate the effects and possible mechanisms of transcutaneous neuromodulation (TN) in patients with chronic constipation. Twelve patients were recruited. The treatment consisted of 2-week TN and 2-week sham-TN which was performed in a crossover design. Bowel habit diary, Patient Assessment of Constipation Symptom (PAC-SYM), Patient Assessment of Constipation Quality of Life (PAC-QOL), and anorectal motility were evaluated. Electrocardiogram was recorded for the assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
102
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(116 citation statements)
references
References 35 publications
13
102
0
1
Order By: Relevance
“…A watch‐size digital stimulator (SNM‐FDC01, Ningbo MedKinetic Inc., Ningbo, China) was built and used to deliver electrical stimulation via these two electrodes using trains of pulses as follows: train on‐time of 2 s and off‐time of 3 s, pulse width of 0.5 ms, pulse frequency of 25 Hz, and current intensity at the maximum level tolerated by the subject (the subject sensed stimulation but could tolerate the test without distraction). This set of parameters was previously shown to improve gastric motility in our lab . For transcutaneous electrical stimulation, the actual current delivered into the acupoint is dependent on the impedance between the electrode and acupoint; whereas, the impedance varies among different subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A watch‐size digital stimulator (SNM‐FDC01, Ningbo MedKinetic Inc., Ningbo, China) was built and used to deliver electrical stimulation via these two electrodes using trains of pulses as follows: train on‐time of 2 s and off‐time of 3 s, pulse width of 0.5 ms, pulse frequency of 25 Hz, and current intensity at the maximum level tolerated by the subject (the subject sensed stimulation but could tolerate the test without distraction). This set of parameters was previously shown to improve gastric motility in our lab . For transcutaneous electrical stimulation, the actual current delivered into the acupoint is dependent on the impedance between the electrode and acupoint; whereas, the impedance varies among different subjects.…”
Section: Methodsmentioning
confidence: 99%
“…To make the stimulation more uniform, we have chosen to use the sensation of the subject to set the strength of the TEA. This method has been used in a number of previous studies …”
Section: Methodsmentioning
confidence: 99%
“…The idea that a similar benefit can be achieved in constipation is supported by the findings of two studies using transcutaneous tibial nerve stimulation, both of which reported symptomatic improvement in patients with constipation . In the first study PTNS was given for 1 h twice daily for 2 weeks and in the second study twice weekly for 30 min for 6 weeks . Similar accounts of improved results with an increase in the stimulation frequency have also been reported with gastric pacing for gastroparesis and deep brain stimulation for Parkinson's disease .…”
Section: Discussionmentioning
confidence: 92%
“…Without the need to come to the hospital, the compliance of the TEA is substantially increased. Possibly attributed to these above factors, TEA was reported to be effective in treating GERD, functional dyspepsia, and functional constipation in a few small‐scale single‐center studies . The disadvantage of delivering electrical current superficially to the skin rather than deep into the acupuncture point seemed to be compensated by more frequent administrations of TEA.…”
Section: Types Of Electroacupuncture and Its Deliverymentioning
confidence: 99%
“…Home‐based TEA has also been reported effective in increasing complete spontaneous bowel movement and reducing constipation symptoms in patients with functional constipation in a pilot study. Mechanistically, TEA was found to improve sympathovagal balance, that is, suppression of sympathetic over‐activity and enhancement of vagal tone . Further large‐scale studies are needed to establish the clinical utilization of TEA for treating chronic functional constipation.…”
Section: Ea and Tea Treatments For Gut Dysmotilitymentioning
confidence: 99%